Replication of transformation-defective mutants of the Prague strain of Rous sarcoma virus and isolation of a td mutant from duck-adapted PR-RSV-C - Geryk, J; Mazo, A; Svoboda, J; Hlozánek, I (Folia biologica, 1980)
The replication of transformation-defective mutants of the Prague strain of Rous sarcoma virus subgroup C was studied using roller cultures. Under such conditions, 10(5)--10(6) infectous units of virus per 0.2 ml were produced, as revealed in both the reverse transcriptase and 16Q complementation tests. A new td daPR-RSV-C mutant was isolated from duck-adapted PR-RSV-C. This mutant replicated in roller cultures with equal efficiency as the original td PR-RSV-C. It was verified that td daPR-RSV-C does not transform chicken fibroblasts, is not oncogenic for 3-week-old chickens and has subgroup C host-range specificity. Both td mutants replicate in duck cells and reach the same titres.
Keywords: Avian Sarcoma Viruses; RNA-Directed DNA Polymerase; virová transformace buněk; kultivované buňky; Cells, Cultured; reverzní transkriptasa; Mutation; mutace; Animals; replikace viru; Virus Replication; kachny; zvířata; Ducks; viry ptačího sarkomu; Cell Transformation, Viral